Phosphodiesterase Type 4D Gene Polymorphism: Association with the Response to Short-Acting Bronchodilators in Paediatric Asthma Patients - Malgorzata Labuda; Sophie Laberge; Julie Brière; Denis Bérubé; Patrick Beaulieu; Tomi Pastinen; Maja Krajinovic (Mediators of Inflammation)
Short-acting b2-adrenergic receptor agonists are commonly used bronchodilators for symptom relief in asthmatics. The aim of this study was to test whether genetic variants in PDE4D gene, a key regulator of b2-adrenoceptor-induced cAMP turnover in airway smooth muscle cells, affect the response to short-acting b2-agonists. Bronchodilator responsiveness was assessed in 133 asthmatic children by % change in baseline forced expiratory volume in one second (FEV1) after administration of albuterol. The analyses were performed in patients with airway obstruction (FEV1/FVC ratio below 90%, n=93). FEV1  % change adjusted for baseline FEV1 values was significantly different between genotypes of rs1544791 G/A polymorphism (P=0.006) and −1345 C/T (rs1504982) promoter variation (P=0.03). The association remained significant with inclusion of age, sex, atopy, and controller medication into multivariate model (P=0.004 and P=0.02, resp.). Our work identifies new genetic variants implicated in modulation of asthma treatment, one of them (rs1544791) previously associated with asthma phenotype.